2017
DOI: 10.1136/bjsports-2016-097372.104
|View full text |Cite
|
Sign up to set email alerts
|

A History of Concussions Is Associated With Symptoms of Common Mental Disorders in Former Male Professional Athletes Across a Range of Sports

Abstract: BackgroundRecent reports suggest that exposure to repetitive concussions in sports is associated with an increased risk of symptoms of Common Mental Disorders (CMD) and of later development of neurodegenerative diseases, in particular chronic traumatic encephalopathy (CTE).ObjectiveTo explore the relationship between sports career-related concussions and the subsequent occurrence of symptoms of CMD among former male professional athletes.DesignCross-sectional analyses performed on baseline electronic questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…In the case of NFL football players, injury emerges as an occupational hazard that exposes healthy young men to increased risk of functional limitations as they age. This is similar to the cases of many other collision sport athletes (e.g., boxing, roller derby, ice hockey, soccer, lacrosse, rodeo, full-contact martial arts; Segen’s Medical Dictionary , 2011) who may equally be at risk for premature functional decline and potentially elevated depressive symptoms (Gouttebarge, Aoki, Lambert, Stewart, & Kerkhoffs, 2017; Hume et al, 2017; Manley et al, 2017; Marshall et al, 2015). Improved understanding of risks for depressive symptoms in former NFL athletes may serve as a potential model for pain, functional status, and aging to support efforts in depression treatment and intervention.…”
supporting
confidence: 74%
“…In the case of NFL football players, injury emerges as an occupational hazard that exposes healthy young men to increased risk of functional limitations as they age. This is similar to the cases of many other collision sport athletes (e.g., boxing, roller derby, ice hockey, soccer, lacrosse, rodeo, full-contact martial arts; Segen’s Medical Dictionary , 2011) who may equally be at risk for premature functional decline and potentially elevated depressive symptoms (Gouttebarge, Aoki, Lambert, Stewart, & Kerkhoffs, 2017; Hume et al, 2017; Manley et al, 2017; Marshall et al, 2015). Improved understanding of risks for depressive symptoms in former NFL athletes may serve as a potential model for pain, functional status, and aging to support efforts in depression treatment and intervention.…”
supporting
confidence: 74%
“…However, long-term effects of SRCs in soccer warrant further long-term exploration, with nearly 27% of all injuries attributed to head trauma and concussion. 1 Gouttebarge et al 11 found that soccer players were 50% more likely to subsequently develop mental disorders, including anxiety, depression, sleep disturbance, and substance abuse. Even more concerning, Beghi et al shared preliminary results at the 71st American Academy of Neurology 4 meeting and reported that approximately double the expected number of professional Italian soccer players were diagnosed with amyotrophic lateral sclerosis (33 cases vs 17 expected) at a median age of 43 years.…”
Section: Discussionmentioning
confidence: 99%
“…4,[12][13][14] In a recent study, professional athletes who had 4 or 5 SRCs over a career were 1.5 times more likely to report symptoms of a variety of common mental disorders, including anxiety, depression, sleep disturbance, and substance abuse. 11 Furthermore, evaluation has been conducted regarding the mechanism of injury leading to SRC and the effect of recent gameplay-related rule changes. For example, the institution of a red card for intentional elbow-head contact in a German professional soccer league in 2006 was found to decrease concussion incidence by 29%.…”
mentioning
confidence: 99%
“…The long-term effects of numerous concussion injuries are currently unknown (Raftery, 2014). However, a history of multiple concussions was associated with increased risk of permanent neurological dysfunctions (Baugh et al, 2012;Mckee et al, 2009), common mental disorders (Gouttebarge, Aoki, Lambert, Stewart, & Kerkhoffs, 2017), and mental health disturbances, including increased aggression and impulsivity (Kerr et al, 2014), in retired athletes. The relative frequency and the potential long-term effects of concussion, underline the need to identify factors that may modulate the risk of concussion in rugby.…”
Section: Introductionmentioning
confidence: 99%